Validitas Sosial Etika dalam Interaksi Pesantren di Media Sosial terhadap Persepsi Masyarakat - Moch. Zainul Hasan (Visionaria: Journal of Educational Innovation Management, 2025)
This study aims to explore the management of ethical issues in dealing with social media crises by Islamic boarding schools (pesantren), focusing on strategies implemented to maintain institutional reputation and public trust. The research adopts a qualitative approach with a case study design, selecting Pesantren Nurul Jadid as the subject due to its active social media presence and experience in managing various digital crises. Data were collected through semi-structured interviews with social media administrators and pesantren leaders, observations of the pesantren's social media activities, and analysis of digital documents such as posts, comments, and responses to emerging issues. Data analysis employed thematic techniques, identifying relevant patterns from the collected data and triangulating them to ensure validity. The findings reveal that pesantren face dilemmas in balancing social media trends with religious values, challenges in ethically responding to diverse audiences, and a lack of structured crisis management strategies. These findings underscore the importance of value-based social media crisis management to uphold the integrity of religious institutions in the dynamic digital era.